A State-Of-The-Art Perspective on the Characterization of Subterranean Estuaries at the Regional Scale - Moosdorf, Nils; Böttcher, Michael Ernst; Adyasari, Dini; Erkul, Ercan; Gilfedder, Benjamin S.; Greskowiak, Janek; Jenner, Anna-Kathrina; Kotwicki, Lech; Massmann, Gudrun; Müller-Petke, Mike; Oehler, Till; Post, Vincent; et al. (Frontiers in Earth Science, 2021)
Subterranean estuaries (STEs), the subsurface mixing zones of terrestrial groundwater and seawater, substantially influence solute fluxes to the oceans. Solutes brought by groundwater from land and solutes brought from the sea can undergo biogeochemical reactions, often mediated by microbes, which determine the composition of fluids discharging from STEs (e.g., submarine groundwater discharge), which may have consequences showing in coastal ecosystems. While at the local scale (meters), processes have been intensively studied, the impact of STE processes on solute fluxes to the coastal ocean remains poorly constrained at the regional scale (kilometers). In the present communication, we review the processes that occur in STEs, focusing mainly on fluid flow and biogeochemical transformations of nitrogen, phosphorus, carbon, sulfur and trace metal. We highlight the spatio-temporal dynamics and measurable manifestations of those processes. The objective of this contribution is to provide a perspective on how tracer studies, geophysical methods, remote sensing and hydrogeological modeling could exploit such manifestations to estimate the regional-scale impact of processes in STEs on solute fluxes to the coastal ocean.